English for Specific Purposes in Kosovo’s Private Language Centers: Availability, Market Demand, and Challenges - Veliu Lushaku, Florijana (International Journal of Language and Literary Studies, 2026)
This study investigates the types of ESP availability, teachers’ preparedness, institutional capacity and learners’ perspectives in private language centers in Kosovo. A mixed-methods approach was employed, involving 25 administrators of private language centers, 50 English teachers and 75 learners. Quantitative data were collected through structured questionnaires and analyzed using descriptive statistics, while qualitative data from semi-structured interviews and open-ended responses were examined through thematic analysis. Findings indicate that most private language centers in Kosovo offer at least one ESP course, while Business English and English for Information Technology emerging as the most widely available and most-in demand fields, both showing a noticeable increase over the past five years, reflecting current labor market priorities. Although 78% of teachers reported limited formal ESP training methodology, they demonstrated strong professional autonomy by adapting internet-based and authentic materials to meet learners’ workplace needs. Institutional challenges were substantial: 84% of administrators reported outdated teaching materials, 75% identified insufficient funding for professional development, 60% noted learners’ weak general English proficiency, and 52% reported limited cooperation with employers. Learners’ responses confirmed that ESP is primarily pursued to improve workplace communication and career advancement, while many respondents reported initial difficulties in verbal communication in professional settings. The study highlights a widening gap between labor market expectations and instructional capacity in Kosovo’s private language sector. It offers practical implications of curriculum development, teacher training, and industry collaboration in a transitional educational context.